Verpleging van die geestesvertraagde kind in die gemeenskap - S.J. Moolman (AOSIS, 1985)
There is a shift in emphasis in nursing care of the mentally retarded child in the community. Firstly, the child must be identified and then his condition is evaluated, usually by a multi-disciplinary team. A decision must then be made whether the child will be cared for in the community. The nurse assists the parent or guardian in training for independence which includes self-care, use of toilet, personal hygiene, and dressing. Training in various perceptual and motor skills are also included in the nursing care plan. The nurse makes follow-up visits to evaluate progress and adapts the nursing care plan as necessary. She also has an important role in encouraging and guiding the parents. Nursing the mentally retarded child in the community requires specialised knowledge - and a lot of love.